2022
DOI: 10.1038/s41598-022-20188-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cosmos, Crotalaria, Foeniculum, and Canavalia species, single-cropped or mixes, on the community of predatory arthropods

Abstract: Some plants can attract natural enemy by offering resources such as alternative food and refuge. However, studies need to be conducted before agricultural landscape diversification is implement. Our objective was to determine the best floristic compositions of cosmos (Cosmos sulphureus—Asteraceae), showy rattlepod (Crotalaria spectabilis—Fabaceae), fennel (Foeniculum vulgare—Apiaceae), and jack bean (Canavalia ensiformis—Fabaceae) to attract and maintain predatory arthropods, and know the potential of these tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Conversely, the highest abundance of Araneidae (predators), Staphylinidae (litter transformers), and Termitidae (ecosystem engineers) was observed in the soil ecosystem without any organic residue inputs (control treatment). It is important to consider the prey–predator relationships among these families (Staphylinidae‐Araneidae and Termitidae‐Araneidae) as standard relationships (Barros et al., 2022), given that the organic matter content does not increase as rapidly as in systems managed with organic residues like mulching and compost. In our study, the input of organic residues determined the abundance of specific functional groups (habitat‐dependent vs. resource‐dependent), as well as the dynamics of prey–predator relationships and feedback interactions among soil, P. pyrifolia stands, soil organisms, and their environment (Maillard et al., 2023; Rodriguez‐Ramos et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the highest abundance of Araneidae (predators), Staphylinidae (litter transformers), and Termitidae (ecosystem engineers) was observed in the soil ecosystem without any organic residue inputs (control treatment). It is important to consider the prey–predator relationships among these families (Staphylinidae‐Araneidae and Termitidae‐Araneidae) as standard relationships (Barros et al., 2022), given that the organic matter content does not increase as rapidly as in systems managed with organic residues like mulching and compost. In our study, the input of organic residues determined the abundance of specific functional groups (habitat‐dependent vs. resource‐dependent), as well as the dynamics of prey–predator relationships and feedback interactions among soil, P. pyrifolia stands, soil organisms, and their environment (Maillard et al., 2023; Rodriguez‐Ramos et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…В Европу вид был завезен в 1791 году и продемонстрировал широкий потенциал для возделывания в качестве покровной и лубяной культуры (6,17). В настоящее время запущен проект BECOOL (https://www.becoolproject.eu/) для оценки потенциала выращивания нетрадиационных лигноцеллюлозных культур в диверсифицированных севооборотах на территории Европы (18,19).…”
Section: рис 2 географическое распространение культуры Crotalaria Jun...unclassified
“…Crotalaria has been shown to produce sufficient dry matter to cover and protect the soil from potential erosion, as well as providing nitrogen in amounts useful for subsequent harvests of crops in a diversified crop rotation (D. Scott et al, 2022, A.P. Barros et al, 2022). In the United States, the plant occupies one of the leading places in the list of intermediate cover crops.…”
Section: фгбну всероссийский нии сельскохозяйственной микробиологииmentioning
confidence: 99%
“…Another plant that supports the habitat of predators and parasitoids is Cosmos. Barros et al [17] found that Cosmos sulphureus was associated with Araneidae, Eutichuridae, Oxyopidae, and Thomisidae. Insect pollinators such as A. cerana, and A. mellifera have also been reported to visit the sulfur cosmos [17].…”
Section: Flower Visitor Insectsmentioning
confidence: 99%